ANALISIS TIPOLOGI TUTUPAN VEGETASI SEBAGAI DASAR PENYUSUNAN STRATEGI RESTORASI DI AREA IUPHHK-RE PT REKI - Nining Nurfatma; Prijanto Pamoengkas; Ika Heriansyah (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2017)
Harapan rainforest situated in South Sumatera is a restoration area of PT REKI company that highly susceptible to land conversion. The problem faced in the effort of restoration is the restorated area that is too large and has not been tested any silvicultural techniques. The condition of land cover is the basic information that could be used as a reference in the preparation of restoration strategy. The study aimed to determine the level of damage, the condition of the ecosystem, appropriate silvicultural techniques, and plant species restoration priorities. The used methods were analysis of vegetation in 4 typologies (secondary forest, old shrub, young shurb, former akasia plantations), and the analysis of Normalized Difference Vegetation Index (NDVI). The results showed that the correlation between density value (y) and NDVI (x) was: y = -136.35+425.46x, R2 (0.89). The order of  area with the level of damage from the lowest to the highest were: the typology of secondary forest, old shurb, young shrub, and former akasia plantation, respectively. The typology of secondary forests had the highest value of diversity, richness, and evenness  (H’>3, Dmg>5, and E>0.6). Relationship between former akasia plantations typology and another tipologies was not germane (euclidean distance> 3.31), and the relationship between seedling and trees in all typologies (with the exception of former akasia plantations) was  very high  (r> 0.9). Silvicultural techniques that could be done include eradicating A. mangium in the former akasia plantation and planting in the all typologies with the exception of secondary forest. The plants that could be used for restoration are Macaranga sp., K.malaccensis,  Nephelium sp., P.gutta, H.mengarawan, S.leprosula.